'Bobo-Newton Syndrome': An Unwanted Gift from Man's Best Friend. Issue 4 (2013) - Popiel, Kristin Y; Vinh, Donald C
Abstract : Capnocytophaga canimorsus is a facultative Gram-negative bacillus that is typically a constituent of the oral flora of dogs and cats. It was first isolated by Bobo and Newton in 1976 from a man presenting with meningitis following a dog bite. Transmission to humans follows various animal-related injuries, which may be gross or subtle. C canimorsus can cause a spectrum of syndromes ranging from skin and soft tissue infection to invasive disease such as meningitis or endocarditis. The present article reports a case of C canimorsus meningitis in a patient with the classic risk factor of alcoholic liver cirrhosis. Clinical suspicion was confirmed by culture and genetic identification of the blood isolate. The present article reviews the Capnocytophaga genus, the clinical syndromes most commonly associated with this zoonotic organism, its laboratory identification and treatment.